Pengaruh Sikap, Pelayanan, Kesadaran Wajib Pajak Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan - Dian Pertiwi; Iing Lukman; Indah Lia Pupsita (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2017)
Income taxes are one state revenues significantly affect development in Indonesia.Taxes are one source of financing development in order to improve society. There aredifferent types of taxes to the community however, from some of which tax on land andbuilding is a type of tax and strategic potential as a source of state revenue in order to financethe implementation of government and development. This study aims to determine the effectof attitudes, Services, Awareness and Knowledge of Taxation Taxpayer Against TaxpayerCompliance In Pay Tax And Building. The analytical method used in this research is multiplelinear regression analysis using SPSS Version 20. The population in this study is a mandatoryproperty tax registered at the district office Bangko Merangin regency, Jambi. The number ofcompulsory tax on land and buildings by 5117 taxpayers in 2015. The sample in this studywere 100 respondents with incidental Sampling methods. The findings in this study indicatethat the attitude of the taxpayer, the taxpayer awareness and knowledge of taxation have asignificant impact on tax compliance in paying property taxes as well as tax service factors donot significantly influence taxpayer compliance in paying property taxes.